UMP welcomes its Fourth Vice-Chancellor - UMP, PNC (2019)
Professor Ir. Dr. Wan Azhar Wan Yusoff has been appointed as the new Vice-Chancellor for Universiti Malaysia Pahang (UMP) for three years with effective from May 16, 2019 until May 15, 2022.